Plurilinguisme(s) et appropriation du français par des adultes migrants - Émilie Lebreton; Eric Mercier (Recherches en didactique des langues et des cultures)
Language training for adult migrants is characterized by various recommendations which show a relative openness to plurilingualism. For the teachers and learners we met in our research, plurilingualism and the didactics that can result from it can be viewed in different ways depending on experiences, projects and conceptions of languages as well as the teaching-learning of French in this context of training-insertion. In the course of the discussions, it appears that the teaching of plurilingualism cannot be considered in terms of educative tools used by teachers and learners, neither in terms of good or bad practices that would lead to prescribe/proscribe plurilingualism. From an appropriative approach, to reflect didactics of plurilingualism means to rely on experiences, on their meanings and on the transformations they generate.